Theories of Consciousness and Emergent Technologies: The Impact of Personality on Approaches to Change and Choice - Benjamin, Colin; Bitetto, Paul (Advances in Social Sciences Research Journal, 2023)
This article delves into the nature of consciousness, aiming to reconcile conflicting theories beyond dualism and panpsychism by addressing differences between early and late adopters of emerging technologies. We propose a new perspective on the integrity of consciousness that transcends binary divisions and embraces the unity of all life forms. Their contributions embrace the interplay between subjective and objective elements, acknowledging that changes and choices arise from complex interactions between known and unknown broader systemic influences. Appreciating the synthesis of traditional and progressive elements, alternative thinkers encourage a dynamic and balanced perspective, where truth is not confined to a singular perspective but emerges from the richness of diverse viewpoints. This paves the way for a more inclusive and comprehensive understanding of attitudes and opinions fostering a greater appreciation for the intricate interconnectedness of life’s complexities.